1968
DOI: 10.1210/jcem-28-4-503
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Activity in the Serum of Rabbits Immunized with Thyroid Microsomes

Abstract: Rabbits were immunized with human thyroid microsomes in an effort to determine if thyroid-stimulating activity would develop in their serum. Twenty-four of 32 rabbits so immunized developed significant amounts of thyroid-stimulating activity, while only 1 of 8 control animals, immunized with liver or adrenal microsomes, had such a response. Peak thyroidstimulating activity appeared in most instances one week after the course of immunization; it usually declined thereafter. Repeated courses of immunization resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1968
1968
1978
1978

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…(J Clin Endocr 29: 231,1969) E VIDENCE indicating that the longacting thyroid stimulator (LATS) is involved in the pathogenesis of Graves' disease has been extensively discussed (1,2). The hypothesis that LATS is an antibody to a thyroid antigen (3), has received support from the finding of thyroid-stimulating activity in the serum of rabbits immunized with human thyroid tissue (4)(5)(6)(7). A significant correlation between LATS and high titers of antithyroglobulin antibodies has been found in patients with active Graves' disease (8,9).…”
mentioning
confidence: 99%
“…(J Clin Endocr 29: 231,1969) E VIDENCE indicating that the longacting thyroid stimulator (LATS) is involved in the pathogenesis of Graves' disease has been extensively discussed (1,2). The hypothesis that LATS is an antibody to a thyroid antigen (3), has received support from the finding of thyroid-stimulating activity in the serum of rabbits immunized with human thyroid tissue (4)(5)(6)(7). A significant correlation between LATS and high titers of antithyroglobulin antibodies has been found in patients with active Graves' disease (8,9).…”
mentioning
confidence: 99%
“…There are several reports of LATS crossing the placenta (McKenzie, 1964;Sunshine et al, 1965), which are compatible with LATS being an antibody. Further, gamma globulin antibody having thyroid stimulating activity is produced by immunization of rabbits with human thyroid cell fraction (Beall and Solomon, 1968;McKenzie, 1968). In previous experiments, we were unable to detect a "LATS" antigen by the passive cutaneous anaphylaxis technique or the indirect immunofluorescent method, and to this time , no clear immunological reaction has confirmed that an antigen for LATS is present in the components of the thyroid cell (Ochi and DeGroot, 1968).…”
mentioning
confidence: 81%
“…The antibody binding of thyroxine (T4) in active thyroid immunity, a phenomenon originally described in this laboratory based on electrophoretic distribution of radiothyroxine in immune sera ( l ) , has now been confirmed in various other laboratories (2)(3)(4)(5)(6). Miore recent investigations in obese strain chickens have also shown binding of thyrmine by spontanmusly forming thyroid autoantibodies (7).…”
mentioning
confidence: 84%
“…In passive immunity there is no exogenous antigen challenge or de novo antibody synthesis, rather antibodies from an immune subject or an animal are merely transferred to another individual either naturally (e.g., passage of antibody gamma globulin, IgG, through the placenta) or artificially through exogenous administration. 3 On leave from the Radiobiology Division, Atomic Energy Establishment, Cairo, Egypt. T4-thyroid antibody interaction, we have carried out some in vitro tests of thyroid function simultaneously with paper electrophoretic studies in the sera of thyroglobulinimmunized animals.…”
mentioning
confidence: 99%